A check-in system supporting multiple attendees check-in at a time by proximity-based methods - Sae-Lim, Nopparut; Sinchai, Ananta; Yiangsupapaanontr, Nathan; Tuwanut, Panwit (My University, 2021)
Every year, tons of events are held. One essential problem of each event is a check-in process. The check-in process wastes plenty of time because each check-in unit is able to check only single participant at a time. Diverse approaches using proximity-based methods have been developed to lessen the check-in processing time. To improve the check-in processing time, these methods are surveyed in this paper. The survey has found that most proximity-based schemes still verify attendees in the same manner but consume lesser time. In addition to the survey, a solution that offers a check-in system that is capable of checking in multiple attendees at a time is proposed. The proposed solution employs beacon technology which is already installed on most mobile devices to provide a unique electronic ticket for each device. With this presented solution, each participant already having the unique electronic ticket on his/her device registered is automatically checked in when walking into an event venue. This significantly helps reduce time consumed in the check-in process.
Keywords: Check-in system; Event management; Mobile application; Proximity-based methods; Web application